THE RELATED FACTORS TO NATIONAL HEALTH INSURANCE PARTICIPATION IN THE CATEGORY OF NON-WAGE WORKERS IN THE WORK AREA OF PUSKESMAS GILIRENG, PASELLORENG VILLAGE, GILIRENG DISTRICT, WAJO 2020 - Aditya Aryandi; Sitti Raodhah; Syarfaini Syarfaini; Syamsul Alam; Surahmawati Surahmawati (Homes Journal = Hospital Management Studies Journal, 2022)
The National Health Insurance is a program launched by the Indonesian government since 2004 with the issuance of National Law No.40 of 2004 concerning the National Social Security System (SJSN) which mandates that social security is mandatory for all residents including National Health Insurance through a National Security Administration. Social as manager of the Health Insurance system. In Indonesia, data shows that in 2019 BPJS Kesehatan participants were 221,580,743 out of 267.6 million people in Indonesia.This research was conducted to determine the factors related to the level of JKN participation in the PBPU category in Paselloreng Village. This research is a quantitative study with an observational analytic approach with a cross sectional study design and a sample size of 204 respondents who were taken by means of Accidential Sampling.The results of the study using the chi square test showed that the factors associated with the JKN participation in the category of Non-Wage Workers were Knowledge (p-value = 0,000), income (p-value = 0.001), Number of Family Members (p-value = 0.024), Perception (p-value = 0,000) and motivation (p-value = 0,000), while the variable not related to JKN participation in the category of Non-Wage Workers in Paselloreng Village is Last Education (p-value = 0.187), Occupation (p-value = 0.760 , and distance of access to BPJS Health services (p-value = 0.097). Suggestions from this study are expected for the government and society to pay more attention to the things that cause the lack of public participation in JKN such as difficult access to services, equal distribution of contribution assistance. inaccurate, inadequate information, and encouragement for the public to participate in JKN.Keywords: Healthcare BPJS, JKN, Non-Wage Workers, Independent Participants, Non- Participants